Literary manifestation Days of Gordana Brajović as the initiator of literary creation by primary school students - Jovanović Aleksandar M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2013)
Literary manifestation Days of Children's Poetry and Work by Gordana Brajović has been held in Aleksinac for fourteen years. During this time, twelve poetry collections appeared containing awarded and praised students' works. The literary papers are divided into three age categories: from the first to the fourth grade, from fifth to the eight grade and secondary school. Several thousand contributors from Serbia and abroad have taken part in this manifestation so far. In terms of literary genre, the first category is mostly dominated by lyrical poems. It can also be noted that at this age students use various narrative techniques as well. The second age category reports larger variety of genre through the presence of drama, report, treaty, essay and recount.